Functional annotation of genes of Pinus sylvestris associated with resistance to phytopathogenic micromycetes - Mozharovskaya, Ludmila V. (Experimental Biology and Biotechnology, 2019)
On the basis of the obtained data of next generation sequencing of Scots pine seedlings transcripts, high expressed loci were selected. Analysis of the results obtained in the GenBank NCBI database made it possible to identify families of genes associated with resistance to phytopathogenic microorganisms: glycosylhydrolase (GH19), heat shock proteins Hsp70 and Hsp90, antimicrobial polypeptides (AMP), calcium-binding proteins (CBP); alpha-amylase inhibitors, lipid transfer proteins, seed storage proteins (AAI-LTSS). Also, two EST markers with an unidentified function were identified, characterized by a high degree of similarity to the sequences of the previously described resistance genes PsACRE and polypeptides having antifungal activity (SS/AF).
Keywords: scotch pine; next-generation sequencing; transcriptome; resistance genes; phytopathogenic organisms